Estimation of Above Ground Carbon Stocks in Green Areas of PT Sumatra Prima Fibreboard, North Indralaya, Ogan Ilir, South Sumatra - Wulandari, Ayu; Zulkifli, Hilda; Setiawan, Doni; Laksana, Agung (Program Pascasarjana Universitas Sriwijaya, 2024)
Abstract: PT Sumatera Prima Fibreboard (PT SPF) is a private company that produces medium-density fibreboard (MDF). PT SPF made a green area in several locations in the factory environment as an effort to reduce air pollution, especially CO2 gas due to MDF production activities. The function of green area as a carbon pool has an important role in reducing and suppressing the release of CO2 emissions into the air. This research aims to determine the value of biomass and stored carbon reserves in saplings, poles, and trees rates, as well as understorey, and litter in PT SPF's green areas. This research used stratified purposive sampling methods. The saplings, poles, and trees biomass used non-destructive method by recording the species, and the diameter at breast height. Understorey and litter biomass measurements used destructive method by taking parts of the understorey and litter above the surface as samples. Based on this research, there were 13 saplings, poles, and trees rates species belonging to 9 families and 13 understory species belonging to 11 families in the research plots. The potential for saplings, poles, trees, understorey, and litter carbon storage in 5 green areas of PT SPF with total area of 16,673 m2 (1.67 ha) is 471,20 tons and classified as a good category.